Traumatic Brain Injury A Clinician's Guide to Diagnosis, Management, and Rehabilitation - Tsao, Jack W.; Tsao, Jack W. (Springer New York : Imprint: Springer, 2012)
Traumatic brain injury (TBI) is a major cause of disability worldwide. Each year 1.7 million new TBIs occur in the United States, and it is also considered a signature injury of the Iraq and Afghanistan conflicts. Despite the relatively high incidence-within both civilian and military populations-the diagnosis and treatment, particularly of mild TBI/concussion, remains an inexact science. Traumatic Brain Injury: A Clinician's Guide to Diagnosis, Management, and Rehabilitation is a concise guide designed for neurologists, primary care, and sports physicians and other medical providers, psychologists and neuropsychologists, and athletic trainers who may evaluate and care for patients with TBI. The book features summaries of the most pertinent areas of diagnosis and therapy, which can be readily accessed by the busy clinician/professional. In addition, the book's treatment algorithms provide a highly practical reference to cutting edge therapies.  A superb contribution to the literature, Traumatic Brain Injury: A Clinician's Guide to Diagnosis, Management, and Rehabilitation offers a well-designed, well-written, useful resource for all providers who treat patients with TBI.